Production of Powder Grease for Wire drawing - Hassan, Ameera; Shanaa, Renad; Alawna, Sandy; Sarhan, Tasneem (My University, 2015)
Wire drawing is a metal working process used to reduce the cross section of wire by pulling the wire through single or series of drawing dies. This process needs aid to ease drawing and minimize the friction between produced product and machine die, that can be achieved by using dry grease powder and the most common type is calcium soap (calcium stearate). This product is required by many companies work in this field like Al- Shark Electrode company which is specialist in wire drawing for many applications, the powder grease used by them is not manufactured in Palestine and is imported from foreign countries at high cost, for that this project aims to produce the powder by different economical and efficient techniques. In this project calcium stearate was prepared by different methods either direct reaction of lime with fatty acid or converting sodium stearate to calcium stearate. For both methods the calcium carbonate was supplied from two sources, local market and a waste from stone cutting plants (stone cutting waste). By direct method, six samples were prepared, two of them were succeeded and the others were failed. On the other hand, eleven samples were prepared by indirect method, eight of them have succeeded technically but the others were failed. Some tests like PH, solubility, ash content, DSC test, and the appearance were applied on the success samples from each method. According to the results of these tests, one sample has been chosen which was (ID7), because it has good properties, it’s a hard powder, insoluble in water, with melting temp 129.87ᵒC and softening temp 73.92ᵒC, the ash content was 21% and with a PH equal 6.5. Also it has the lowest raw materials cost between all samples, which is 1.95NIS/Kg. This price is competitive compared to the price of the imported calcium grease. The total consumption of this powder in Palestine was 100 ton/year with a selling price of 4,800 NIS/ton. The feasibility study for a plant producing powder grease carried out based on the above information, the capital investment was 15900NIS, and net profit was 85,945.24NIS/year, cash flow of 91,845.24NIS/year and payback period equal 9.5 years. The growth of production with a rate of 5% for the next 3 years was assumed